Two Methods of Discharge Care Program Follow-up on Drug Treatment Adherence of Patients with Heart Failure - Seyedeh Fateme Isazadeh; Mehdi Khabazkhoob; Fatemeh Monjazebi; Fariba Borhani (Mashhad University of Medical Sciences, 2024)
Background: Heart failure is a potentially life-threatening condition that disrupts the normal flow of blood throughout the body. Patients with heart failure lack sufficient knowledge regarding drug treatment adherence. An effective discharge plan and its continuity can improve treatment adherence.Aim: This study was performed with aim to compare two methods of discharge care program follow-up on drug treatment adherence of patients with heart failure.Method: This quasi-experimental was conducted in 2022-2023 on 126 patients with heart failure in Iran. Participants were divided into the two intervention groups via telephone call (group A), and via video message (group B) and a control group (group C). The required data were collected through Morisky Medication Adherence Scale (MMAS-8) before and 12 weeks after the start of the intervention. In the intervention groups, the care plan was presented to the patients every two weeks.Results: The mean drug treatment adherence scores increased to 2.47±1.68 in group A, 1.51±2.11 in group B, and 0.83±1.60 in group C,  which was significantly different in each group and among the three groups (p<0.001). The Mean changes in the patient's drug treatment adherence in group A were statistically significant only compared to group C (p<0.001). After adjusting confounding variables (age, gender and cause of heart failure), there was a significant difference among the three groups in the patient's drug treatment adherence and quality of life (p=0.002).Implications for Practice: According to the obtained results, the nurses are recommended to continue the care program after discharge and use technologies to improve treatment adherence.